2016
DOI: 10.1002/ird.1964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irrigation Volume and Saline Water On Maize Yield and Soil in Southern Italy

Abstract: A field experiment was carried out in southern Italy to investigate the effects of irrigation and salinity on a maize crop and soil properties. The experiment was laid out comparing different irrigation rates (I1, I2, I3—re‐establishing 50, 75 and 100% of the calculated maximum evapotranspiration) and water quality (FW, fresh water and SW, saline water). Grain yield was significantly greater by 60% in 2008 than in 2010. No significant difference was shown for grain yield between the irrigation treatments, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 44 publications
1
14
1
1
Order By: Relevance
“…The reduction rate was gradually decreased with the increase of the rate of application of irrigation water (5% in I 3 treatment). However Leogrande et al (2016) found no significant difference for grain yield between the irrigation treatments, whereas water productivity decreased significantly with increasing irrigation rates.…”
Section: Shoot Dry Weightmentioning
confidence: 66%
“…The reduction rate was gradually decreased with the increase of the rate of application of irrigation water (5% in I 3 treatment). However Leogrande et al (2016) found no significant difference for grain yield between the irrigation treatments, whereas water productivity decreased significantly with increasing irrigation rates.…”
Section: Shoot Dry Weightmentioning
confidence: 66%
“…Similarly, grain quality parameters of important cereal crops, such as wheat (Triticum durum Desf. and Triticum aestivum L.) [28][29][30], rice (Oryza sativa L.) [31], or corn (Zea mays L.) [32], could be improved by applying salinity, depending on the specific conditions and cultivars. However, decreased wheat [30,33] or rice [34] grain quality in addition to yield decline under salt stress conditions has also been reported.…”
Section: Soil Salinity and Plant Interactionsmentioning
confidence: 99%
“…Then again, the authors stressed, to avoid aggressive salt accumulation in soil, it is well worth to interchange thsaline and fresh water irrigation (Liu et al, 2016). By some accounts, the maize irrigation with water high in water-soluble salts did not decrease its yield and even increased the proteins content in it to 9.1% (Leogrande et al, 2016). Thus, the irrigation with salt-saturated water is still open to question and unresolved.…”
Section: -mentioning
confidence: 99%